A TiO2 Coated Carbon Aerogel Derived from Bamboo Pulp Fibers for Enhanced Visible Light Photo-Catalytic Degradation of Methylene Blue - Jian Zhang; Wei Yuan; Tian Xia; Chenghong Ao; Jiangqi Zhao; Bingxue Huang; Qunhao Wang; Wei Zhang; Canhui Lu (Nanomaterials, 2021)
Carbon aerogels (CA) derived from bamboo cellulose fibers were coupled with TiO2 to form CA/TiO2 hybrids, which exhibited extraordinary performance on the photo-catalytic degradation of methylene blue (MB). The structure and morphology of CA/TiO2 were characterized by field emission scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and Raman spectrum. The CA displayed a highly porous and interconnected three-dimensional framework structure, while introducing the catalytic active sites of TiO2 onto the aerogel scaffold could remarkably enhance its photo-catalytic activity. The adsorption and photo-catalytic degradation of MB by the CA/TiO2 hybrid were investigated. The maximum adsorption capacity of CA/TiO2 for MB was 18.5 mg/g, which outperformed many similar materials reported in the literature. In addition, compared with other photo-catalysts, the present CA/TiO2 demonstrated superior photo-catalytic performance. Almost 85% of MB in 50 mL solution with a MB concentration of 10 mg/L could be effectively degraded by 15 mg CA/TiO2 in 300 min.